Pengaruh Program Gemar Membaca terhadap Kemampuan Mengarang Siswa Kelas IV SD - Saidah, Hakimah (Mimbar Sekolah Dasar, 2017)
The reading program is another name for reading literature used by SDN Bugangan 02Semarang. Implementation of the program likes to read that is 15 minutes before the learning activities of students reading books with the title as he wishes. In this study students are given a book entitled "a collection of children's stories about the habit of eating healthy food". This short story contains six titles of children with a theme of healthy food. This theme is in accordance with the 9th grade theme teacher's book. This study aims to determine the effect of reading programs on the ability to make students. This research uses Pre-Experiment Designs with quantitative approach. The sample of this research is all students of grade IV SDN Bugangan 02 Semarang. The results of this study indicate that reading programs affect students' writing ability.